Habitat relations of Rhea americana in an agroecosystem of Buenos Aires Province, Argentina - Herrera, Lorena Paola (2004)
The maintenance of wild populations of Greater Rhea (Rhea americana) through effective management requires an understanding of their habitat requirements in terms of vegetation composition and field configuration. We studied the relative influence of some anthropogenic variables (presence of route, house and fences) and resource variables (presence of water source, composition and coverage of plant species, vegetation height and bare soil), on the habitat use by a population of rheas in a cattle ranch of Buenos Aires Province, Argentina. Habitat use was determined indirectly by documenting the number of faeces in summer, autumn–winter and spring 1999. The presence or absence of faeces was related to the measured variables through discriminant analysis that allowed the elaboration of predictive models of habitat use by this species. Contrary to what was expected, those variables related to human activity showed a low predictive value on the habitat use by rheas when compared with resource variables. Rheas preferentially selected the stream area in all seasons and sites with great percent cover of Bupleurum sp., Phyla canescens, Sida leprosa, Plantago lanceolata, Trifolium repens, Lolium multiflorum, Stipa spp., and Stenotaphrum secundatum. Low vegetation height was another important component of rhea´s habitat in summer and autumn–winter. The high accuracy level obtained by validation tests of this model supports its utility for the management of rhea populations in other cattle ranches of the region, and to analyze the suitability of other ranches for reintroduction programs.